2017
DOI: 10.18632/oncotarget.16438
|View full text |Cite
|
Sign up to set email alerts
|

Connexin40 controls endothelial activation by dampening NFκB activation

Abstract: Connexins are proteins forming gap junction channels for intercellular communication. Connexin40 (Cx40) is highly expressed by endothelial cells (ECs) of healthy arteries but this expression is lost in ECs overlying atherosclerotic plaques. Low/oscillatory shear stress observed in bends and bifurcations of arteries is atherogenic partly through activation of the pro-inflammatory NFκB pathway in ECs. In this study, we investigated the relation between shear stress, Cx40 and NFκB. Shear stress-modifying casts we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…Moreover, Cx40 has been shown to interact with IκBα. Their binding dampens NFκB nuclear translocation and, in consequence, endothelial activation (6). Many more players of the endothelial Cx interactome remain to be identified in the years to come.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Cx40 has been shown to interact with IκBα. Their binding dampens NFκB nuclear translocation and, in consequence, endothelial activation (6). Many more players of the endothelial Cx interactome remain to be identified in the years to come.…”
Section: Discussionmentioning
confidence: 99%
“…In general, Cx37 and Cx40 are abundantly expressed in ECs of large arteries, whereas Cx43 and Cx45 are found in their SMCs (2,3). Detailed en face immunofluorescence studies revealed that Cx37 and Cx40 are highly expressed in ECs of straight parts of arteries that are exposed to high laminar shear stress and that these Cxs are downregulated in ECs at arterial branch points or bifurcations subjected to a disturbed blood flow (6,7,8). In contrast, the expression of Cx43 is induced in ECs exposed to disturbed flow (3,7), as illustrated in Fig.…”
Section: Figurementioning
confidence: 99%
“…Moreover, the sequestration of the transcription factor specificity protein (Sp)-1 in the cytoplasm of bone marrow stromal cells after expression of Cx43 and Cx45, was demonstrated to impact C-X-C motif chemokine (CXCL)-12 synthesis [30]. Along these lines, hijack of the nuclear factor kappa B (NF-κB) transcription factor by Cx40 has been shown to inhibit its nuclear translocation and initiation of proinflammatory signaling, thus ascribing to Cx40 a vital role upon endothelial homeostasis [31]. In addition, interaction of Cx32 with the scaffolding protein Discs Large homolog 1 (Dlgh1) at the plasma membrane was suggested to block cell cycle progression in hepatocytes [32].…”
Section: The Role Of Cx43 As a Scaffolding Complexmentioning
confidence: 99%
“…In contrast to Cx43, Cx40 expression has been reported to protect against atherosclerosis in mice by synchronizing endothelial anti-inflammatory signaling thus inhibiting leukocyte recruitment to the atherosclerotic lesion [ 42 ]. Interestingly, Cx40 expression is induced in arterial ECs by high laminar shear stress, as normally observed in straight parts of arteries that are known to be protected from atherosclerosis [ 43 ]. IκBα, a member of a protein complex inhibiting the activation of the transcription factor NFκB, was recently identified as a binding partner of Cx40-CT.…”
Section: Role Of Cxs and Panxs In Distributing Arteries And Atheromentioning
confidence: 99%
“…IκBα, a member of a protein complex inhibiting the activation of the transcription factor NFκB, was recently identified as a binding partner of Cx40-CT. The Cx40 interactome may be relevant for the control of NFκB activation in arterial ECs and the initiation of atherogenesis [ 43 ].…”
Section: Role Of Cxs and Panxs In Distributing Arteries And Atheromentioning
confidence: 99%